Analysis of bionic riblet structures` influence on centrifugal pump performance - Pawar, Rajendra Jibhau; Ray, Milind P.; Suryawanshi, Shubham Rajendra; Dond, Dipak Kisan (Zielona Góra: Uniwersytet Zielonogórski)
The growing need for energy conservation and sustainability in industrial sectors has led to extensive research on improving mechanical systems, particularly centrifugal pumps. These pumps play a crucial role in hydropower generation, industrial processes, and fluid transportation. This study explores the use of biomimetic riblet structures inspired by shark skin to enhance centrifugal pump performance. Traditional designs focus on either hydraulic efficiency or noise reduction, leaving room for improvement. By developing and experimentally testing a bionic impeller, the research examines its impact on head, power consumption, and efficiency across different flow rates. While biomimetic adaptations are common in aerospace and marine engineering, their potential in pumps remains underexplored.
Keywords: bionic impeller; centrifugal pump; biomimetic riblet structure; shark skin